Proposta de um modelo para mensuração de confiança em redes horizontais de empresas - Campos, Elaine Aparecida Regiani de (2016)
This study aims to propose and to apply a model to measure trust among companies belonging to a horizontal cooperation network. For this, a Systematic Literature Review (RBS) process was developed, using Methodi Ordinatio, forming a portfolio of qualified 78 papers, base for the model development. From this portfolio, three prospects for analysis of trust emerged: Barriers, Externalities and trust-building factors, which unfolded in 8 dimensions, 17 factors and 54 variables. Weighting was done to dimensions. To this, the Analytic Hierarchy Process (AHP) multicriteria decision method was used. Two instruments of research were created in order to assess the perceptions and expectations of companies in relation to the trust factor between the components of a horizontal network of companies. The model was applied in a horizontal collaborative network in TI sector. After this Cronbach's alpha test was used for checking the instrument's internal consistency. The model showed to be easy to apply with the application of the model, it was realized that it is easy to apply, and it allowed to devise a scenario in accordance with the perception, that is, the practices observed by entrepreneurs, and expectations also assessing barriers externalities and factors. It was possible to perceive, for the network studied, that there is trust between partners, however to perceptions exceed expectations, it is necessary to develop actions to encourage partners to cooperate in this network has a successful and the bonds of trust may be higher.